Penggunaan Permainan Tradisional Congklak Modifikasi untuk Meningkatkan Kemampuan Mengenal Angka Pada Anak Usia Dini - Alpira S. Nupura; Sitriah Salim Utina; Sitti Rahmawati Talango (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
The ability to recognize numbers is one of the important aspects in early childhood cognitive development that is the basis for mathematical thinking skills at a later stage. However, the results of initial observations in Group A of PPAUDIT Lukmanul Hakim Gorontalo Regency show that the ability to recognize children's numbers is still low because learning tends to use conventional methods that are less interesting. This research aims to improve children's ability to recognize numbers through the use of modified traditional congklak games. The research uses the Kemmis and McTaggart model Class Action Research (PTK) which consists of the stages of planning, implementing actions, observation, and reflection. The research subjects amounted to 19 children consisting of 9 boys and 10 girls. The data collection technique was carried out through observation and documentation, while the data analysis used percentage descriptive analysis. The results of the study showed an increase in the ability to recognize numbers in each cycle. At the preliminary stage, the average ability of children reached 36.40% in the category of Starting to Develop (MB). After the implementation of the modified traditional game of congklak in Cycle I, the average increased to 78.94%, and in Cycle II it reached 100% with the category of Very Good Development (BSB). Improvements occur in aspects of logical thinking, the ability to solve problems flexibly, and symbolic thinking through the recognition of numbers. Thus, the modified traditional game of congklak has proven to be effective in improving the ability to recognize numbers in early childhood.